Comportamiento del empleo en empresas privadas formales de diez a más trabajadores en la región Loreto periodo abril - julio 2016-2020 - Noriega Pezo, Juan Manuel (2021)
The research work on employment behavior in formal private companies with ten to more workers in the Loreto region, April-July 2016-2020 period, had as its main objective to analyze the employment growth rate in formal private companies with ten to more workers in the Loreto region, in the period April - July of the years 2016 -2020, it is descriptive level with a quantitative approach of non-experimental design and longitudinal cut, the sample was made up of all the records on the employment index in all economic activities in formal companies with ten more workers in the Loreto region, period April July 2016 - 2020, which are in the archives of the Central Reserve Bank, Ministry of Labor and Employment Promotion and the National Institute of Statistics and Informatics. The work concludes that the employment growth index in all economic activities in the months and period of analysis has been negative, which indicates that jobs in formal companies have decreased mainly in the primary activity that encompasses the sub-branches agriculture, fishing and hydrocarbons. The impact of the pandemic in 2020 has been considerable in the months of April and May, where more than 9,000 jobs were lost, thereby creating more poverty and informality